Efektivitas Mediasi Terhadap Perselisihan Pemutusan Hubungan Kerja Pada Dinas Perindustrian Dan Tenaga Kerja - Ekawati, Margareta Dany; Subekti, Rahayu (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
This article aims to analyze whether mediation for the settlement of disputes over termination of employment in Department of Industry and Labor of Sukoharjo has been effective enough or hasn’t been effective also to find out the obstacles that have been encountered by the mediators while handling the mediations in in Department of Industry and Labor of Sukoharjo. This article uses empirical legal research method by directly examining research from the field and the nature of the research and the approach used is descriptive analytic.The result of this study indicates that the mediation for the settlement of disputes over termination of employment in Department of Industry and Labor of Sukoharjo hasn’t been effective enough, especially on law factor and cultural factor. In addition, the obstacles that have been encountered by mediators while handling the mediations are first, both parties stand on their own opinion and no one wants to settle down that makes it harder to find the solution, second, the employers can not attend the assembly, third, the employers are hard to cooperate with, lastly, the Covid-19 pandemic that is still spreading.